The Role of the Weimar Triangle in the Processes of European Integration in 1991–2004 (Economic and Political Thought, 2018)
In the year 1989 Poland began to reform its political and economicsystem. In parallel it started to implement the processes of Europeanization.Rapprochement with the western structures became the main objective ofthe Polish foreign policy. The ultimate goal was the full membership of theNATO and European Union. The Weimar Triangle was established in August1991, it was one of the tools which should help Poland in achieving thisobjective. Regular meetings of Ministers of Foreign Affairs and other Polish,German and French politicians took place within this area of cooperation.In the article I analyse the actual impact of this form of cooperation on theprocesses of European integration in the years 1991–2004.
Keywords: Weimar Triangle, Poland, Germany, France, European Union, European integration, political changes